Timing analysis and optimization of sequential circuits - Maheshwari, Naresh, 1970- (Kluwer Academic, 1999)
Timing Analysis and Optimization of Sequential Circuits describes CAD algorithms for analyzing and optimizing the timing behavior of sequential circuits with special reference to performance parameters such as power and area. A unified approach to performance analysis and optimization of sequential circuits is presented. The state of the art in timing analysis and optimization techniques are described for circuits using edge-triggered or level-sensitive memory elements.